ANALYSIS OF DIGITAL TECHNOLOGY AS A BUSINESS STRATEGY TO INCREASE SALES TURNOVER FOR CULINARY MSMES IN BANJARNEGARA - Purbandari, Yenny; Maesaroh, Siti (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2025)
Indonesia's economy is significantly underpinned by the growth of Micro, Small, and Medium Enterprises (MSMEs), with culinary MSMEs in particular playing a substantial role in local economic development. Amidst rapid technological advancements and evolving consumer behavior, these businesses face considerable challenges in enhancing sales and maintaining market competitiveness. Digital transformation offers a strategic solution to these issues, providing MSMEs with greater opportunities to expand their market reach and boost sales. However, many MSMEs continue to operate conventionally due to limited knowledge, a lack of experience with digital technology, and poor internet access. The purpose of this research is to examine how Banjarnegara's culinary MSMEs' sales turnover has been affected by digital marketing, digital payment methods, and online food delivery services.  In all, 342 companies were considered for this study, but only 78 were ultimately chosen at simple random sampling technique.  Multiple linear regression was used to examine the gathered data.  The results show that online food delivery services, digital marketing, and digital payments all significantly impact sales turnover, and that this effect is largely both partially and simultaneously.